Pendidikan Perkoperasian bagi Pengurus, Pengelola dan Anggota Koperasi di Daerah Istimewa Yogyakarya, Kota Surakarta, dan Kota Bandung - Lulus Setiawan, Wawan (E-Coops-Day, 2024)
The cooperative education activities held this time have a specialty, namely that they are carried out in synergy with the 2024 Indonesian Cooperative University Student Field Practice activities. These activities are carried out by lecturers at the Indonesian Cooperative University who serve as Field Practice Supervisors by off-line at the field practice location, or lecturers who do not guide field practice by on-line. Cooperative educational activities that synergize with Field Practices provide reinforcement of the meaning and benefits of Field Practice Activities both for cooperatives and for students participating in Field Practices. The activity was attended by 14 lecturers at the Indonesian Cooperative University and went well and achieved the program objectives.